Prenatal Diagnosis in a Fetus With X-Linked Recessive Chondrodysplasia Punctata: Identification and Functional Study of a Novel Missense Mutation in ARSE - Zhang, Li; Hu, Haoran; Liang, Desheng; Li, Zhuo; Wu, Lingqian (Frontiers in Genetics, 2021)
X-linked recessive chondrodysplasia punctata (CDPX1) is a rare skeletal dysplasias characterized by stippled epiphyses, brachytelephalangy, and nasomaxillary hypoplasia, which is caused by the function loss of arylsulfatase E (ARSE, also known as ARSL). Pathogenic mutations in ARSE were usually responsible for CDPX1 in newborns or adults, while there were few prenatal reports. In our study, a novel missense mutation (c.265A>G) in ARSE was identified in a fetus with short limbs by using whole exome sequencing (WES). Bioinformatic algorithms predicted that the mutation is harmful, and following RT-qPCR, western blotting and enzymatic assay were performed to further analyze the pathogenicity of variant. The results showed that the variant could lead to reduced transcription and protein expression and the loss of enzymatic activity. To sum up, the novel mutation c.265A>G in ARSE was considered to be the genetic cause for the affected fetus. We report a prenatal case in Chinese population with functional analysis of ARSE, which not only helps the family to predict recurrence risks for future pregnancies but also provides more information for understanding this rare disease. The research also shows that WES is a feasible method in prenatal diagnosis for those fetuses with CDPX1.